Development of multiplex PCR assay for the detection of five non-halal species in Islamic foods / Md. Abdur Razzak - Razzak, Md. Abdur (2015)
Food forgery is one of the most concerning socio-economic issues having impact on health, religions and hard earned wages. The recent scandals on horse meat in Europe, rat meat in China have given consumers apprehension on the detection, differentiation and identification of ingredients, especially the meat items, in foods, medicine and other consumers’ products. A range of analytical methods based on lipid, protein and DNAbiomarkers have been proposed for meat species authentication. However, lipid and protein-based examinations are less trustworthy since protein can be easily denatured and the level of lipids can be significantly modified through the processing treatments. On the other hand, universal information content and extraordinary stability of DNA even under compromised conditions have given it a strong foundation to serve as traceable biomarkers in all forensic investigations. Among the DNA-based detection schemes, polymerase chain reaction (PCR)-based methods are highly appreciated because of its extraordinary power of target amplification from few copies to easily detectable quantities. Multiplex PCR assays are especially interesting since they allow the detection of multiple species targets in a single assay platform, saving cost and time. This study is the first endeavor to develop a multiplex PCR system for the detection of five potential “haram” meat species, namely pig, dog, cat, rat and monkey species, in a single assay platform under raw, processed, mixed and commercial matrices. We developed here five different sets of primers targeting mitochondrial ND5 gene for pig and monkey; ATPase 6 gene for dog and rat and cytochrome b gene for cat species. These primers specifically amplified 172, 163, 141, 129 and 108 bp fragment of cat, dog, pig, monkey and rat species from pure and complex matrices. Cross-species amplification was checked by performing species-specific PCR against 21 commercially important land and aquatic species and no cross-amplification was detected. The limit of detection (LOD) of the developed multiplex system was 0.01 ng for rat, monkey and dog and 0.02 ng DNA for cat and pig species. In admixed samples and commercially processed foods, the tested LOD of 0.1% target meats. The developed multiplex system unambiguously detected target meat species under raw and heat-treated (autoclaved at 121 °C and 45 psi for 2.5 h) pure and admixed samples. Screening commercial food products further attested the assay validity under complex matrices. Short-sized target amplicons and extraordinary stability and sensitivity of the developed multiplex PCR system suggested that the assay could be used by regulatory bodies of food authentication and wildlife protection.